Aproveitamento de levedura residual cervejeira como substrato na produção integrada de Beta-glucana e biomassa micelial - Heringer, Holdai Carlos Emerich (2023)
Large amounts of brewer's residual yeast are generated in the beer production process, and this biomass is rich in carbohydrates, proteins, soluble nitrogen, vitamins, and minerals, which favors its use as a substrate in microbiological platforms. Spent brewer's yeast was studied as a low-cost alternative feedstock for sustainably producing a high-added-value microbial β-D-glucan (lasiodiplodan). The potential of using the mycelial biomass (single cell-protein) generated in the production of β-glucan was also evaluated as a strategy of integrated biorefining. Five cell lysis protocols were studied to obtain a nutrientrich yeast cell lysate, with enzymatic hydrolysis being the most efficient, with results of 46.29 g 100 g-1 of soluble intracellular components and 65.8 g 100 g-1 of soluble protein. Mineral supplementation of the fermentation medium was assessed, and the single-cell protein (SCP) produced was characterized by the nutritional composition, amino acid, and lipid profiles. Lasiodiplodia theobromae MMPI was effective in the co-production of lasiodiplodan ((1→6)-β-D-glucan)) and SCP in a medium consisting of sucrose (60 g L-1), cell lysate (7 g L-1 of total proteins), MgSO4.7H2O (0.5 g L-1) and K2HPO4 (0.5 g L-1). Enzymatic hydrolysis with Alcalase promoted more significant cell rupture and greater release of soluble intracellular components compared to other cell lysis processes studied. Mycelial biomass obtained was rich in protein (30,54 g 100 g-1) and contained all essential amino acids with high concentrations of leucine (69 mg g-1), lysine (62,2 mg g-1), valine (44,2 mg g-1) and threonine (43,2 mg g-1). Co-production of lasiodiplodan and SCP by the fungus L. theobromae MMPI may be an economically promising bioprospecting alternative.